2018
DOI: 10.1037/pac0000303
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in masculine honor beliefs predict attitudes toward aggressive security measures, war, and peace.

Abstract: We hypothesized that individual differences in masculine honor beliefs (MHBs) would predict participants' views of the world and the potential for evil and good among the people in it, as well as their attitudes toward war, peace, and aggressive security policies. Participants' levels of MHBs were positively associated with their support for war and aggressive security policies (Studies 1 and 2), as well as beliefs in pure evil and perceptions of the world as a competitive jungle (Study 2), and they were negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Crucially, the support and tendency for aggression among men in honor states appear to be limited to honor-related violence-where aggression is used as a means to defend and maintain one's reputation-rather than violence in general (Cohen & Nisbett, 1994). For instance, honor-endorsing individuals tend to be more supportive of violent actions by the U.S. military (Barnes et al, 2014;Saucier, Webster, et al, 2018), especially in response to terrorist attacks (Barnes, Brown, & Osterman, 2012).…”
Section: Cultures Of Honor and Aggressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, the support and tendency for aggression among men in honor states appear to be limited to honor-related violence-where aggression is used as a means to defend and maintain one's reputation-rather than violence in general (Cohen & Nisbett, 1994). For instance, honor-endorsing individuals tend to be more supportive of violent actions by the U.S. military (Barnes et al, 2014;Saucier, Webster, et al, 2018), especially in response to terrorist attacks (Barnes, Brown, & Osterman, 2012).…”
Section: Cultures Of Honor and Aggressionmentioning
confidence: 99%
“…Relatedly, this area of work would also benefit from distinguishing honor-based masculinity from masculinity norms found in other potentially related subcultures, such as the military and warrior culture (Anestis et al, 2019;Bryan & Morrow, 2011;Lancaster et al, 2018). Not only are honor-endorsing individuals more supportive of military action (Barnes et al, 2014;Barnes, Brown, & Osterman, 2012;Saucier, Webster, et al, 2018), but individuals from U.S. honor cultures may be overrepresented in the U.S. military (Brown, 2016;Council on Foreign Relations, 2020;Watkins & Sherk, 2008). Thus, future research could examine honor endorsement among U.S. military members and its potential impact on aggression and suicide.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Furthermore, the MHBS has been used to examine relationships between adherence to MHB and various attitudes and perceptions of social behaviors, such as perceptions of the world being a “competitive jungle” (Saucier, Webster, et al, 2018), men’s motivations for muscularity (Saucier, O’Dea, & Stratmoen, 2017), perceptions of slurs against men’s masculinity as insulting and deserving of retaliatory aggression (Saucier, Till, Miller, O’Dea, & Andres, 2015), expectations for men to physically confront honor threats (O’Dea, Chalman, Castro Bueno, & Saucier, 2018), and negative perceptions of those who do not (O’Dea, Bueno, & Saucier, 2017). MHB are associated with various political attitudes, including greater endorsement of agentic male candidates for President of the U.S. (Martens, Stratmoen, & Saucier, 2018), negative perceptions of football players who knelt during the National Anthem to protest police violence against racial minorities (Stratmoen, Lawless, & Saucier, 2018), and greater support for restrictive national security policies and endorsement of war (Saucier, Webster, et al, 2018). Furthermore, MHB are associated with negative perceptions of rape survivors and increased support for punishment for rapists (Saucier, Strain, Hockett, & McManus, 2015), as well as with perceptions of romantic rejection as threatening men’s honor and consequently expecting increased aggression by men toward women who reject their romantic advances (Stratmoen, Greer, Martens, & Saucier, 2018).…”
Section: Masculine Honor Beliefsmentioning
confidence: 99%
“…Webster and Saucier (2013) developed an individual difference scale of belief in pure evil (BPE). Individuals who more strongly believe in pure evil see the world is a viler, more dangerous place, and report more aggressive (vs. peaceful) attitudes, from issues about foreign policy to the criminal justice system (Campbell & Vollhardt, 2013;Saucier et al, 2018;Vasturia et al, 2018;Webster & Saucier, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Webster and Saucier (2013) developed an individual difference scale of belief in pure evil (BPE). Individuals who more strongly believe in pure evil see the world is a viler, more dangerous place, and report more aggressive (vs. peaceful) attitudes, from issues about foreign policy to the criminal justice system (Campbell & Vollhardt, 2013; Saucier et al, 2018; Vasturia et al, 2018; Webster & Saucier, 2013, 2015). Two studies have shown that people who believe more in pure evil more greatly: supported harsher punishments for various crimes (murders, assault, stealing), advocated for the death penalty, and opposed criminal rehabilitation, even after controlling for attributional complexity (the tendency to think more deeply about the causes for others' behavior), just‐world beliefs, and pessimism (Webster & Saucier, 2013).…”
mentioning
confidence: 99%